METTL14-mediated m6A modification of DDIT4 promotes its mRNA stability in aging-related idiopathic pulmonary fibrosis - Dan Li; Li Qian; Yufeng Du; Lifang Liu; Ziyue Sun; Yongkang Han; Xiangrui Guo; Chao Shen; Zheng Zhang; Xuejun Liu (Epigenetics)
Although N6-methyladenosine (m6A) may be related to the pathogenesis of fibrotic process, the mechanism of m6A modification in aging-related idiopathic pulmonary fibrosis (IPF) remains unclear. Three-milliliter venous blood was collected from IPF patients and healthy controls. MeRIP-seq and RNA-seq were utilized to investigate differential m6A modification. The expressions of identified m6A regulator and target gene were validated using MeRIP-qPCR and real-time PCR. Moreover, we established an animal model and a senescent model of A549 cells to explore the associated molecular mechanism. Our study provided a panorama of m6A methylation in IPF. Increased peaks (3756) and decreased peaks (4712) were observed in the IPF group. The association analysis showed that 749 DEGs were affected by m6A methylation in IPF. Among the m6A regulators, the expression of METTL14 decreased in IPF. The m6A level of our interested gene DDIT4 decreased significantly, but the mRNA level of DDIT4 was higher in IPF. This was further verified in bleomycin-induced pulmonary fibrosis. At the cellular level, it was further confirmed that METTL14 and DDIT4 might participate in the senescence of alveolar epithelial cells. The downregulation of METTL14 might inhibit the decay of DDIT4 mRNA by reducing the m6A modification level of DDIT4 mRNA, leading to high expression of DDIT4 mRNA and protein. Our study provided a panorama of m6A alterations in IPF and discovered METTL14 as a potential intervention target for epigenetic modification in IPF. These results pave the way for future investigations regarding m6A modifications in aging-related IPF.